ENEDINA ALVES MARQUES: FIRST BLACK ENGINEER IN BRAZIL - Canavarro Benite, Anna M. (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2020)
Enedina Alves Marques was born on January 13, 1913. Only girl among 10 brothers. Daughter of a maid, she was raised in the family home for whom her mother worked. In 1927, he started studying at the Escola Normal where he attended until 1931, graduating from the Normal course. She was the first woman and the first black woman to graduate in Civil Engineering in Brazil, challenging academic and social standards.